HUSSERL'S PHENOMENOLOGY OF PRACTICAL REASON. - Laurukhin, Andrei (Problems / Problemos, 2015)
This research paper offers an analysis of Husserl's early theory of action in its two forms -- as the scientific ethics and theory of values and as the phenomenology of will. The author focuses his attention on two issues: the issue of parallelism between logic and ethics, and the issue of how independent Husserl is in his comprehension of ethical issues and elaboration of the idea of practical reason from the conception and methodological premises of transcendental phenomenology -- or, on the contrary, how dependent he is on those premises.